Geometrical characterization of single layer silicon based piezoresistive microcantilever using ANSYS - Zakaria, Mohd Hazrul; Bais, Badariah; Ab. Rahim, Rosminazuin; Yeop Majlis, Burhanuddin (2012)
In this paper, characterization on the geometrical aspects of a single layer, p-doped silicon based piezoresistive microcantilever using finite element method is presented. The displacement and the von Mises stress obtained from the simulation were observed by varying the geometries of the microcantilever namely the thickness, length, width and the distance between the piezoresistor legs. The sensitivity of the microcantilever was then calculated and tabulated. From the simulation results, it can be shown that the displacement and sensitivity of the single layer piezoresistive microcantilever is comparable to the dual layer counterpart with the thinner microcantilever resulted in a maximum displacement and sensitivity, compared to other geometrical factors.